(untitled) (Research, Society and Development, 2022)
According to the literature, prostate cancer is considered the second most prevalent type of neoplasm in the male population, affecting mainly those with non-modifiable risk factors, such as advanced age and family history of the disease. Therefore, the objective of this study was to evaluate morbidity and mortality from prostate cancer in different Brazilian regions, through the analysis of absolute numbers and hospitalization and mortality rates. This is an ecological, retrospective, descriptive study with a quantitative approach. Data were obtained from the electronic address of the Department of Informatics of SUS/DATASUS and categorized into numbers of hospitalizations and deaths from Malignant Prostate Neoplasia, distributed in the five Brazilian regions and presented in the form of absolute numbers and rates. Within the period comprised in the study, from 2016 to 2020, it was observed that the North region has the highest mortality rates and the lowest rates of hospitalization for prostate cancer. In this way, it is pointed out that the limited demand of the male population for health services, as well as the existing prejudice and fear in relation to the digital rectal exam, impair early diagnosis and, consequently, the timely and effective treatment of prostate cancer. Therefore, health services should emphasize care actions aimed at the health of this public, developing strategies and offering services that prioritize the reduction in the levels of morbidity and mortality resulting from this pathology and promote equality in care.